Pengaruh Daun Seledri Dalam Bentuk Jus Dan Air Rebusan Terhadap Penurunan Kadar Asam Urat Pada Lansia Di Desa Tanjung Alam - Margareta Andika, Rindy Arabella; Umamy, Farida (Cattleya Darmaya Fortuna, 2022)
Uric acid is the final product of purine metabolism in the form of nucleoprotein, which is one of the nucleic acid components found in the nuclei of body cells. Celery boiled water containing apiin and apigenin is believed to lower uric acid levels naturally without causing side effects. This study aims to examine the effect of boiled celery water on reducing uric acid levels in the elderly. Research aim: The aim of this research is to identify the effect of giving boiled celery water on reducing uric acid levels in the elderly in Tanjung Alam Village in 2023. Method: The research used pre-experiment with One Group Pretest Posttest design. The sampling technique was simple random sampling technique. The total sample was 66 elderly peopleResults: Results of statistical analysis using the Paired T-Test. The results of the Paired T-test on 66 elderly people showed a decrease in uric acid levels with a p-value of 0.000 (p < 0.05). This shows that there is an effect of boiled celery water on reducing uric acid levels in the elderly. Conclusion: Based on the research results, there is an effect of giving boiled celery water on reducing uric acid levels in the elderly. This therapy can be used to reduce uric acid levels in the elderly by doing it regularly with 200 cc every morning.